4d+2(d+6)=-3(d-4)

Simple and best practice solution for 4d+2(d+6)=-3(d-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4d+2(d+6)=-3(d-4) equation:


Simplifying
4d + 2(d + 6) = -3(d + -4)

Reorder the terms:
4d + 2(6 + d) = -3(d + -4)
4d + (6 * 2 + d * 2) = -3(d + -4)
4d + (12 + 2d) = -3(d + -4)

Reorder the terms:
12 + 4d + 2d = -3(d + -4)

Combine like terms: 4d + 2d = 6d
12 + 6d = -3(d + -4)

Reorder the terms:
12 + 6d = -3(-4 + d)
12 + 6d = (-4 * -3 + d * -3)
12 + 6d = (12 + -3d)

Add '-12' to each side of the equation.
12 + -12 + 6d = 12 + -12 + -3d

Combine like terms: 12 + -12 = 0
0 + 6d = 12 + -12 + -3d
6d = 12 + -12 + -3d

Combine like terms: 12 + -12 = 0
6d = 0 + -3d
6d = -3d

Solving
6d = -3d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '3d' to each side of the equation.
6d + 3d = -3d + 3d

Combine like terms: 6d + 3d = 9d
9d = -3d + 3d

Combine like terms: -3d + 3d = 0
9d = 0

Divide each side by '9'.
d = 0

Simplifying
d = 0

See similar equations:

| -6v-4=-4(v-3) | | -71p+2p-9p+2+43= | | y=(-.0625)x^2+.375x+(-2.05) | | -6v-4=4(v-3) | | -6v-4=-4v(v-3) | | 10(3x-1)=-100 | | 3(v+3)=-8v-2 | | -16+x=8 | | 3y+48=-3(y+2) | | (16q+4)+42=29q+20 | | (-2+v+y)(-9)= | | 5x(12-5)-9=36 | | 2x-10=3x-35 | | -5=-5y+3(y+5) | | 4ln(x-2)=-2 | | (x+31)+34=45x+21 | | -6(2x-2u-2)= | | x+2=4-2*x | | -3u+7(u-2)=-22 | | 3m-12=-6 | | 8(v+7)-2v=38 | | -(-2y-x+2)= | | 2x^2-10x=4x | | 8(v+7)+2v=38 | | (1)3.45=3(4.42) | | -1.2+0.15x=0 | | -18p-6(5-4p)=4(p-3)-12 | | 7x^2+151x-1372=0 | | 11y-8=5y+16 | | 8w-3=5w+18 | | ln(x+2)=7-ln(x+2) | | -81=6v-13v-18 |

Equations solver categories